2010
DOI: 10.1002/anie.201001308
|View full text |Cite
|
Sign up to set email alerts
|

Electrons as “Invisible Ink”: Fabrication of Nanostructures by Local Electron Beam Induced Activation of SiOx

Abstract: Beam me up: A novel two‐step process allows iron nanostructures to be generated locally on SiOx/Si at 300 K. The surface is first locally activated by an electron beam. Then the activated structures are exposed to [Fe(CO)5], which decomposes and grows autocatalytically to give pure Fe nanocrystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
121
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(130 citation statements)
references
References 37 publications
7
121
1
1
Order By: Relevance
“…Recently, we demonstrated that the active sites on SiO x are oxygen vacancies generated by electron stimulated desorption. 18,19 This mechanism is also confirmed for the here investigated membrane covered with a native silicon oxide: it was found that a pre-irradiated membrane remains active towards Fe(CO) 5 decomposition for at least one day, with no significant differences of the observed iron deposits. This is a strong indication for a chemical modification (i.e., activation); if simple charging were to play a role, the activity should have decayed after one day.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…Recently, we demonstrated that the active sites on SiO x are oxygen vacancies generated by electron stimulated desorption. 18,19 This mechanism is also confirmed for the here investigated membrane covered with a native silicon oxide: it was found that a pre-irradiated membrane remains active towards Fe(CO) 5 decomposition for at least one day, with no significant differences of the observed iron deposits. This is a strong indication for a chemical modification (i.e., activation); if simple charging were to play a role, the activity should have decayed after one day.…”
supporting
confidence: 84%
“…[14][15][16][17] With electron beam induced surface activation (EBISA), we have recently introduced a FEBIP technique, where no FSE proximity effect occurs. 18,19 Figure 1 schematically depicts the ideal two step EBISA process: In the first step, the surface is irradiated and thereby locally activated with a focused electron beam; in the second step, it is exposed to the precursor iron pentacarbonyl, Fe(CO) 5 . On the activated sites, which are identified as oxygen vacancies, i.e., understoichiometric silica, 19 decomposition of Fe(CO) 5 at room temperature leads to the formation of Fe nuclei, which then grow autocatalytically upon prolonged precursor dosage to form clean, cubic Fe crystals, 18,19 corresponding to bcc aFe.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These developments, and other examples of surface activation [91][92][93][94][95][96][97] and nanostructure editing through nonchemical pathways [99], highlight the wide diversity of processes that can be exploited by electron beam processing techniques. Furthermore, these recent applications illustrate the need for advances in predictive modeling of electron (and ion) beam restructuring of materials in both inert and reactive environments.…”
Section: Discussionmentioning
confidence: 99%
“…4(b)). The technique is a variant of similar methods used to fabricate chemically active surface regions [91][92][93][94][95][96][97], and electron irradiation methods used in surface chemistry studies of phenomena such as electron induced oxidation [98].…”
Section: Applicationsmentioning
confidence: 99%